Durkheim e la sfera culturale cosmopolita - Verderame, Dario (SocietàMutamentoPolitica, 2017)
The article aims to show how the Durkheimian cosmopolitan vision of social reality relies on an aesthetic as well as moral dimension. That emerges from the ritual theory that Durkheim elaborated in The Elementary Forms of Religious Life and, in particular, from the analysis of intertribal ritual practices that the author emphasized as the origin of religious internationalism, typical of Australian Aboriginal societies. The article puts forward two main arguments. The first is to refute the thesis, often associated with Durkheim, that individuals are able to create only exclusionary forms of solidarity by means of rituals. The second is to outline the contribution that Durkheim’s theory of ritual can provide to understand what scholars have defined as the ‘cosmopolitan cultural sphere’ and phenomena related to it, such as festivals.